Integrative COI and morphological analyses reveal a new Falcicornis Planet, 1894 species from Guizhou, China (Coleoptera: Lucanidae) - Xin, Fei-Yi; Yong, Xue-Tong; Chen, Hui-Jia; Ke, Si-Kai; Zhong, Xiao-Tian; Wu, Song-Qing (Zootaxa, 2025)
The present study describes a new species from Guizhou, China, i.e., Falcicornis banjinshuaii Xin, Yang & Zhong, sp. nov., within the F. bisignatus group. The new species can be conspicuously distinguished from its related congeners based on morphological characters and the COI analyses. Additionally, a checklist of genus Falcicornis Planet, 1894 is provided.